Determinants of Pulmonary Tuberculosis Among Inmates in Class IIA Penitentiary in Jambi City - Anggi Syahdia Damanik; Adelina Fitri; Fajrina Hidayati; Helmi Suryani Nasution; Evy Wisudariani; Edo Riyandani (Tecno Scientifica Publishing, 2025)
Pulmonary tuberculosis (pulmonary TB) is a contagious infectious disease caused by Mycobacterium tuberculosis. Pulmonary TB can be fatal for those affected. This study aimed to determine the relationship between comorbidities, contact history, nutritional status, smoking habits, and prison time with pulmonary tuberculosis among inmates. A case-control research design was used, with purposive sampling of 82 inmates from the Class IIA penitentiary in Jambi City in 2024. Data collection took place from January to July 2024. The research variables included age, comorbidities, contact history, nutritional status, smoking habits, and prison time, assessed through interviews, BMI measurement, and tuberculosis diagnosis. The data were analyzed using the Chi-Square test. The results showed that 94.1% of participants were aged 15–64, 91.8% had no comorbidities, 56.5% had a history of contact, 55.3% had a normal BMI (<18.5), 70.5% were smokers, and 83.5% had been incarcerated for more than three months. There was no significant association between pulmonary TB and comorbidities (OR 3.16, 95% CI 0.32–31.7). However, significant relationships were found with contact history (OR 39.27, 95% CI 9.93–155.25), nutritional status (OR 45.04, 95% CI 11.23–180.58), and smoking habits (OR 7.24, 95% CI 2.18–24.08). No significant relationship was observed between pulmonary TB and prison time (OR 3.07, 95% CI 0.75–12.53).